Reduced phosphorus is associated with older age and hypoalbuminemia. Risk factors for all-cause mortality in peritoneal dialysis patients - Ávila, Marcela; Prado, Ma. del Carmen; Cuevas-Budhart, Miguel Ángel; Paniagua, Ramón (Frontiers in Nutrition, 2023)
Introduction/aim Hyperphosphatemia is a mortality risk factor in dialysis patients; however, low phosphorus levels too. Diabetes and malnutrition are strongly associated with mortality and with reduced serum phosphorus. This study analyzed the pattern of serum phosphorus in patients on Peritoneal Dialysis (PD) and its association with mortality. Methods A Secondary analysis was performed on a multicenter cohort study in peritoneal dialysis patients from two previous studies done by our group. Results Six hundred fifty-four patients were included. Serum phosphorus was <3.6 mg/dL in 28.29% of patients, 3.6 to 5.2 mg/dL in 48.16%, and >5.2 mg/dL in 23.55%. In logistic regression analysis; education, age, and hypoalbuminemia were risk factors for low P levels. In multivariate Cox analysis P < 3.6 mg/dL, age, and low albumin were predictors for all-cause mortality. When lower P and lower albumin were combined, this group had the highest risk for all cause and cardiovascular mortality. Conclusion The frequency of patients with reduced serum phosphorus was higher in the Mexican population than in Europe or Asia. Low serum phosphorus levels, older age and hypoalbuminemia were risk factors for all-cause mortality. Low phosphorus combined with low albumin levels were the highest risk factor for all-cause and cardiovascular mortality.